Personal Attributes As Indicators Of Students Leading Competence: A Conceptual Analysis In The Context Of Higher Education - Mardhiyah, Sayang Ajeng; Stiawan, Deris; Meilinda, Meilinda; Pratiwi, Marisya; Iswari, Rosada Dwi (Jurnal Pendidikan Karakter, 2025)
This research aims to formulate a personal attribute profile as an indicator of leading competence for Sriwijaya University students. This research uses a qualitative approach with content analysis and thematic analysis methods of academic literature, national policy documents, university vision and mission, and feedback from stakeholders. Based on the synthesis results, the four personal attribute profiles in this study are growth mindset, academic integrity, critical thinking disposition, and academic buoyancy. These profiles are expected to be integrated in the curriculum and various academic and non-academic activities, and become a strategic step to realize the vision of national higher education, achieve the goals and objectives of Sriwijaya University, and meet the competency demands of the world of work and the global community in the future.